Regulation of human immunodeficiency virus type 1 (HIV-1) mRNA translation. (13th April 2017) - Hidalgo, Laura; Swanson, Chad M.
Abstract : Human immunodeficiency virus type 1 (HIV-1) mRNA translation is a complex process that uses the host translation machinery to synthesise viral proteins. Several mechanisms for HIV-1 mRNA translation initiation have been proposed including (1) cap-dependent, eIF4E-dependent, (2) cap-dependent, cap-binding complex-dependent, (3) internal ribosome entry sites, and (4) ribosome shunting. While these mechanisms promote HIV-1 mRNA translation in the context of in vitro systems and subgenomic constructs, there are substantial knowledge gaps in understanding how they regulate viral protein production in the context of full-length virus infection. In this review, we will summarise the different translation mechanisms used by HIV-1 mRNAs and the challenges in understanding how they regulate protein synthesis during viral infection.